Application of Plant Fertilizer Serum Using Natural Ingredients - Erlangga Dwi Putra; Rafli Fadhilah Baehaki; Muhammad Rizki Ramdhani (International Journal of Research and Applied Technology (INJURATECH), 2022)
In this pandemic period, many people are starting to look for new activities, one of which is planting ornamental plants or other plants. Apart from being an aesthetic building, plants are also able to produce oxygen for the environment around the house. The purpose of this research is to educate every new or existing community. has been involved in growing plants for a long time. The method used is qualitative. The application is done by mixing natural ingredients and then extracting them and giving them to plants by watering or spraying them so that they grow quickly. The results that will appear on plants will grow faster than plants that do not. using serum. The results of this serum will increase plant growth 75% faster than plants that do not use this serum. And the benefits of having a serum can increase plant growth faster than usual and the use of this serum will be safe for plants because it uses natural ingredients and hobbyists or cultivators will quickly get results from these plants.